Communication Motives of Citizen Journalists on Liputan6.com's Citizen6 Channel (Oratio Directa, 2022)
This study examines the communication motives of citizen journalists who contributed to the Citizen6 channel on Liputan6.com. It uses a qualitative descriptive approach based on observation and interviews conducted at the Liputan6.com editorial office on 29 July 2017. The participants comprised a community-development manager and three citizen contributors with student and private-sector employee backgrounds. The analysis relates participants' accounts to Maslow's hierarchy of needs, particularly belonging, esteem, and self-actualization. The findings identify six related motives: pursuing a writing interest, improving skills, sharing useful information, learning from sources, expanding social relations, and gaining pride or recognition from published work. Self-actualization is the dominant interpretive category, while esteem appears through personal pride and public recognition. Citizen6 also functions as an editorial intermediary: contributors can submit everyday stories and feature articles, whereas sensitive or hard-news material is redirected for more specialized verification. The study describes the motives of three contributors in a specific editorial setting; it does not represent all Citizen6 contributors or measure audience effects.
Keywords: Citizen journalism; Communication motives; Citizen6; Online media; Self-actualization